Immunoglobulin-E levels, Interleukin Genes and Atopy - Taha Ashraf Qurashi; Gulzar Ahmad Bhat; Syed Mudassar (Research Aspects in Biological Science Vol. 7, 2022)
The present study was aimed to study the association of Immunoglobulin-E(IgE) and different variants of Interleukin-4(IL-4), and Interleukin-13(IL-13) genes with various types of allergies. A professional staff employed a pre-tested questionnaire to gather all the food, lifestyle, and clinical information. Coagulation and anticoagulation vials were used to collect a 2ml sample of blood from each. Extracted and kept for further use were serum and DNA samples. PCR-RFLP techniques were used for the genotypic study, whereas ELISA was used to assess serum IgE. We observed a statistically significant difference of serum IgE levels among cases and controls (P <0.05). The observed difference of serum IgE levels were retained among subjects who also harboured variant genotypes of IL-4 and IL-13 genes (P<0.05). Furthermore, when allergy risk was stratified based on various clinical characteristics, the above genetic variants significantly altered the risk of allergy. In conclusion, our findings indicate that increased IgE levels, in conjunction with variant forms of the IL-4 and IL-13 genes, are significantly associated with various types of allergies in the study population.